2018
DOI: 10.2139/ssrn.3201031
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of WEIRD Psychology

Abstract: Recent research not only confirms the existence of substantial psychological variation around the globe but also highlights the peculiarity of populations that are Western, Educated, Industrialized, Rich and Democratic (WEIRD). We propose that much of this variation arose as people psychologically adapted to differing kin-based institutions-the set of social norms governing descent, marriage, residence and related domains. We further propose that part of the variation in these institutions arose historically f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 66 publications
1
32
0
2
Order By: Relevance
“…Europeans were the first to develop representative institutions, to hold elections for public office, and to constrain the use of political power by constitutional rules. Exactly why democracy arose in Europe and not elsewhere is a conundrum that we shall not attempt to unravel (for varying perspectives see Cartledge 2016;Schulz et al 2018;Stasavage 2016). We know that it was a long, slow, and halting development, with many reversals and many shifts of course across the continent.…”
Section: Democracy For Europeansmentioning
confidence: 99%
See 1 more Smart Citation
“…Europeans were the first to develop representative institutions, to hold elections for public office, and to constrain the use of political power by constitutional rules. Exactly why democracy arose in Europe and not elsewhere is a conundrum that we shall not attempt to unravel (for varying perspectives see Cartledge 2016;Schulz et al 2018;Stasavage 2016). We know that it was a long, slow, and halting development, with many reversals and many shifts of course across the continent.…”
Section: Democracy For Europeansmentioning
confidence: 99%
“…Europeans also developed and carried with them other features that might be regarded as forming the infrastructure of democracy, e.g., written languages, educational systems, advanced transport and communication systems, urban patterns of settlement, nuclear family structures, nation-states, property rights, capitalist economies, and wealth (comparatively speaking). We do not know which of these features (often associated with the process of modernization) is most important for democracy (Knutsen et al 2018;Murtin, Wacziarg 2014;Schulz et al 2018). But we do know that they developed in tandem and were closely interconnected.…”
Section: Democracy For Europeansmentioning
confidence: 99%
“…Toward a cultural evolutionary neuroscience Psychological and behavioral scientists have recently been forced to grapple with the magnitude of psychological differences across societies (Henrich, Heine, & Norenzayan, 2010a;Muthukrishna, Bell, et al, 2018a;Schulz, Bahrami-Rad, Beauchamp, & Henrich, 2018a). Even mental processes often assumed to be universal and hard-wired have been shown to vary cross-culturally.…”
Section: Oxford Handbook Of Cultural Neuroscience and Global Mental Hmentioning
confidence: 99%
“…There is evidence that West Europeans psychologically adapted to a loose kinship system. Schulz et al (2018) gathered 20 crosscultural measures and found that Westerners are more individualistic and have higher trust, less conformism, and less tolerance of cheating and nepotism. The authors found that this is associated closely with the length of time a population spent under the influence of the Catholic Church.…”
Section: Introductionmentioning
confidence: 99%